Sexual attitudinal conflict and sexual behavior changes among homosexual HIV-positive men - Nilsson Schönnesson, Lena; Clement, Ulrich (Journal of psychology & human sexuality, 1995)
In a German-Swedish coowrative study the HIVa-daptation process, its psychological sequelae and the psychosexual dilemma of homosexual HIV-positive men were investigated. The focus of this article is to highlight conflict solutions of-attitudinal conflict related to sexual behavior changes. The findings indicate that unprotected sex as well as giving up sexual behaviors that are still positively loaded are two examples of conflict solutions. It should also be noted that the conflict is at work even when the individual practices are protected or "safer" sexual behaviors. The results indicate that only referring to sexual behavior data would underestimate the potential of so-called "relapses" to unprotected sexual behaviors.
Elektronische Reproduktion der Druck-Ausgabe 23. Oktober 2008
Gesehen am 22.07.2024